Business directory Davao province 1992. - Silfverberg, Raymunda Rimando; St. Mary's College, Tagum, Davao del Norte (Tagum, Davao Business Resource Center, St. Mary's College, 1992)
Business Directory of Davao Province is the pioneering document for Davao. It is consists of socio-economic profile and list of names and addresses of public and private advertisers of each municipality for the year 1992. This directory promotes the economic status and business in Davao.
A joint undertaking by Business Resource Center, St. Mary's College, Tagum and Raymunda Rimando-Silfverberg.
Keywords: Business enterprises -- Philippines -- Davao del Norte; Davao del Norte -- Commerce -- Directories